Pengelolaan dan Pendampingan dalam Pembuatan Minuman Kunyit Asem Ibu Nurhayati Sebagai UMKM di Desa Takerharjo - Alwian, Bagas (Santri : Journal of Student Engagement, 2024)
Management in making tamarind drinks is one of the momentum that we want, apart from that we can get various opportunities to find out about original products or typical drinks that are produced directly from Takerharjo village. The drink, which is produced directly by "Mrs. Nur Bio", is very popular among the people of Takerharjo village itself, apart from being made without preservatives, sweeteners and flavourings. The management of this turmeric asem drink has been established since 2011 and has been distributed in various shops around Takerharjo. Mrs. Nur Bio is a woman from Takerharjo who is able to prove that she has taken advantage of the existing environment. At the same time, Mrs. Nur Bio is one a model for the Takerharjo community as a way to develop or improve SMEs in Takerharjo village itself. Then the method we use is an observation method which is carried out with assistance and research in the production process.